The role of hepatitis b core as screening test - Mohd Anuar, Ismail (Universiti Sains Malaysia, 2008)
Qualitative detection of antibody to hepatitis B virus core antigen (anti-HBc) is an important aid in diagnosis of acute, chronic, or resolved HBV infection in conjunction with other lab results and clinical information. A multi-center prospective study was conducted to validate the performance of the AxSYM CORE 2.0 assay in a diagnostic population by evaluating precision and performing method comparison. AxSYM CORE 2.0 is a competitive microparticle enzyme immunoassay (MEIA) for use on the AxSYM system for the qualitative detection of anti-HBc in human adult and pediatric serum or plasma. A multi-center prospective study was conducted to validate the performance of the HbsAg and HbsAg Confirmatory assays in a diagnostic population. Assay performance was measured by evaluating precision and performing method comparison. Qualitative detection and confinnation of hepatitis B surface antigen (HbsAg) is an important aid in diagnosis of HBV infection. The HbsAg and HbsAg Confirmatory assays are chemiluminescent microparticle immunoassays for the qualitative detection and confirmation ofHbsAg in human adult. There are about 350 million chronic hepatitis B virus (HBV) carriers worldwide. A proactive approach to the management of this disease is likely to reduce the morbidity and mortality caused by HBV. This study aimed to approach the HB core test as a screening tool in blood bank. The test is designed to rapidly and accurately detect both the HBV surface antigen (HBsAg) and the HBV e antigen (HB Core). A cohort of316 subjects was tested. The serum clinical sensitivity of the hepatitis B sAg or Hb core test was 99.75 and 96.37% for HBsAg and HB Core, respectively. Serum clinical specificity was 99.32% for HBsAg and 98.99% for HB core. Analytical sensitivity was satisfactory for the purposes of population screening. Visual evaluation showed that the test signals were stable for at least 3 h after the recommended evaluation time. No interference or cross-reactivity was observed with known interfering substances and virologic markers. These results indicate that the hepatitis B sAg/ core test is well suited to the accurate detection of HBV carriers. In addition to the good clinical specificity and sensitivity of this test, its stability and user-friendly design mean that a correct performance, even under field conditions, is highly likely. Consequently, the hepatitis B sAg/core test has the potential to identify subjects who require HBV vaccination (HBsAg- and HBeAg-) and HBV -infected individuals who might benefit most from antiviral therapy (HBsAg + and HBeAgl.